2023
DOI: 10.3389/fmars.2023.1188493
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonates disrupt carrageenan synthesis during carposporogenesis in the red seaweed Grateloupia imbricata

Abstract: In this study, we monitored changes in cell wall sulfated galactans in the red seaweed Grateloupia imbricata after the rapid (48 h) induction of cystocarp maturation and carpospore development by the volatile hormone methyl jasmonate (MEJA). Synthesis of sulfated galactans, carrageenans, which requires sulfated UDP galactose, was followed by expression analysis of genes encoding phosphoglucomutase (PGM), galactose-1-phosphate uridyltransferase (GALT), and those responsible for sulfate assimilation (S-transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 32 publications
(39 reference statements)
1
9
0
Order By: Relevance
“…Also, it has been reported that stored polysaccharides play a role in the life cycle [ 8 ] and salinity acclimation of seaweeds [ 19 ]. Therefore, the formation and degradation of floridoside could be interwoven with sulfated polysaccharides, as carrageenan biosynthesis is also dependent on the hexose pool and reproductive stages of red seaweeds [ 3 , 4 ]. Furthermore, it is relevant that GALT expression has been associated with fluctuations in cell wall galactans in the red seaweed Gracilaria changii [ 20 ] whilst GALT expression has also accompanied cystocarp development from induced fertile thalli of G. imbricata treated with methionine ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Also, it has been reported that stored polysaccharides play a role in the life cycle [ 8 ] and salinity acclimation of seaweeds [ 19 ]. Therefore, the formation and degradation of floridoside could be interwoven with sulfated polysaccharides, as carrageenan biosynthesis is also dependent on the hexose pool and reproductive stages of red seaweeds [ 3 , 4 ]. Furthermore, it is relevant that GALT expression has been associated with fluctuations in cell wall galactans in the red seaweed Gracilaria changii [ 20 ] whilst GALT expression has also accompanied cystocarp development from induced fertile thalli of G. imbricata treated with methionine ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is relevant that GALT expression has been associated with fluctuations in cell wall galactans in the red seaweed Gracilaria changii [ 20 ] whilst GALT expression has also accompanied cystocarp development from induced fertile thalli of G. imbricata treated with methionine ( Figure 2 ). Accordingly, the reduced expression of GALT , as a gene precursor of galactan synthesis, has been explained by the contribution of methionine to a pool of sulfur organic compounds in algae, which will affect the expression levels of the genes encoding proteins responsible for the conversion of glucose 6P to 1P by PGM and the transformation to UDP-galactose by GALT [ 3 , 4 ]. Thus, GALT expression is downregulated in ethylene-induced fertile thalli with cystocarps in the early development stage ( Figure 2 A), as well as when late cystocarp development stages are reached in the presence of MEJA ( Figure 2 B).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations